Opalski's syndrome: a rare variant of Wallenberg's syndrome - Sivasamy, Manoj; R., Shreenidhi; M. K., Nishaanth; S., Prasanna Karthik (International Journal of Advances in Medicine, 2022)
A 54-year-old, right-handed male presented with acute-onset severe headache, vertigo, and vomiting. Initial neurologic examination illustrated dysarthria (lingual), nystagmus (horizontal), left dysmetria on finger-to-nose testing, and weakness of the left upper and lower limb. Magnetic resonance imaging showed left lateral medullary infarction (Wallenberg syndrome). The patient was discharged 3 weeks later to an inpatient treatment with neurorehabilitation facility with gradual improvement of his symptoms.